WEAVING BADUY IDENTITY IN MEDIA SIGN OF WEAVING BADUY IDENTITY IN MEDIA “DESA KANEKES” WEBSITE (SPATIAL SEMIOTIC DISCOURSE ANALYSIS) - Santy Yulianti, M.Hum.; Tommy Chirstomy, Ph.D. (Jurnal Bebasan, 2021)
This paper explores the contribution of media in changing the image of an indigenous community by controlling some information of the tribal values possessed by the Baduy tribe in the media. The media that represented Baduy Tribe to the public is called "Desa Kanekes" which invites readers to see the transformation of an isolated tribe into tolerated tribe. Framing in commodification spaces is identified in this media, so that by using discourse framing by Foucault, Barthes's semiology, and commodification by Christ Ryan, this paper will describe and interpret the hidden signs on the website. Baduy‟s identity has unknowingly changed direction from farmers to craftsmen. The website contained articles that certainly support the government program to increase the production of weaving that can support the economic life of the Baduy community. The viewpoint of Baduy life principle which is living a simple and spiritual life is changing through this website. Baduy tribe is directed to become modern indigenous people. This process can be seen on this website that is classified into two spatial codes, i.e. public space and private space. Public spaces are represented in Baduy festival columns and Meretas Mimpi. The private spaces are represented in writing about ritual cultivation and weaving. Ambiguity occurs in most articles because of the unexplained division of custom territory that is the basis of the Baduy interaction boundaries. The identity of the actual Baduy (Inner Baduy) does not receive any portion on this website. This could impact their existence in the future. There is an indication that the Baduy Luar is Baduy thoroughly. This is certainly contrary to the reality.